Cooperative learning in online distance learning: Teacher response - Ramadhan, Syahrul; Atmazaki, Atmazaki; Indriyani, Vivi; Sukma, Elfia (Universitas Ahmad Dahlan, 2022)
It has been almost two years that learning has been carried out online, resulting in students being less social and learning is dominated by individual learning. Therefore, it is necessary to apply group learning to overcome this. However, these lessons cannot be simply applied and need to be analyzed. One of these analyzes is to find out the responses of students and teachers. The purpose of this study was to describe the perceptions of teachers regarding cooperative learning during online distance learning during the COVID-19 pandemic. This research is a descriptive research using survey method. The research instrument was in the form of a questionnaire filled out by 71 teacher respondents. The results showed that several important aspects of cooperative learning were the number of group members, group determination, the media used, and group assessment.